Yeni Yönetimin Ana Unsurları: Yerelleşme, Demokratikleşme ve İl Özel İdaresi - Demirel, Songül (Muş Alparslan Üniversitesi, 2014)
Localization discourses coming to the fore after the eighties gained power with the demands of international organization and had coverage in the legal basis with European Charter of Local Self Government in the nineties. The agreement in which our country made reservation for some of its articles due to our unitary structure seems quite far away from realizing its objectives under the adopted form. Although it was attempted to make arrangements specific to autonomy with various local government reforms in 2000s, it resulted in cancellation by the judiciary. Special Provincial Administration Law No 5302 released in 2005; comprises similar localization cores in respect of followed judicial process and directions of changes made. Some changes in the relationship between provincial general council and governor body draw attention; the head of provincial general council, centralized control method that can be made against the decisions of the head, duration and frequency of assembly etc. evolving situation of provincial general council which is a body established after election will outline the scope of the study. As the origin of decision is based on a body elected its position in historical process of localization will be analyzed.

Seksenli yıllardan sonra gündeme gelen yerelleşme söylemleri, uluslararası örgütlerin talepleriyle güç kazanmış, doksanlı yıllarda Avrupa Yerel Yönetimler Özerklik Şartı ile yasal zeminde yer bulmuştur. Ülkemizin üniter yapısı itibariyle çeşitli maddelerine çekince koyduğu anlaşma, kabul edilen haliyle maksadını gerçekleştirmekten hayli uzak görülmektedir. İkibinli yıllarda ise çeşitli yerel yönetim reformlarıyla özerkliğe özgü düzenlemeler yapılmaya çalışılsada yargı tarafından iptaliyle sonuçlanmıştır. 2005 yılında çıkan 5302 Sayılı İl Özel İdaresi Kanunu; izlenilen yargı süreci ve yapılan değişikliklerin yönü itibariyle benzer yerelleşme nüveleri içermektedir. İl genel meclisi ile valilik organı arasındaki ilişkide bazı değişiklikler dikkat çekmektedir; il genel meclisi başkanının kim olduğu, kararlarına karşı yapılabilecek merkezi denetim şekli, toplanma süresi ve sıklığı gibi. Seçimle gelen bir organ olan il genel meclisinin evrilen durumu çalışmanın kapsamını çizecektir. Kararın menşeinin seçimle gelen bir organa dayanması itibariyle, yerelleşmenin tarihsel sürecindeki yeri analiz edilmeye çalışılacaktır.
Main Elements of New Administration; Localization, Democratisation and Special Provincial Administration
anemon
Keywords: New Administration; localization; democratization; special provincial administration; Yeni Yönetim; yerelleşme; demokratikleşme; il özel idaresi